President’s Message - Frenette, Karen (Operating Room Nurses Association of Canada Journal, 2012)
Welcome to the new ORNAC Journal! I wish to extend my sincere appreciation to the ORNAC’s Editorial Committee, Publisher, and Executive Director for their commitment in making this vision a reality. The new ORNAC Journal can grow and continue to flourish by having submissions from you, our readers. This is your journal! The template is established and you now have the opportunity to contribute. I challenge you to share your research, projects, and clinical articles with fellow perioperative nurses from our country and beyond.